Profiling, exploiting, and countering psychological characteristics in talent identification and development - Cronin, L. D.; Allen, J. B. (The Sport Psychologist, 2015)
The importance of psychological characteristics as positive precursors of talent development is acknowledged in literature. Unfortunately, there has been little consideration of the "darker" side of the human psyche. It may be that an inappropriate emphasis on positive characteristics may limit progress. Negative characteristics may also imply derailment or the potential for problems. A comprehensive evaluation of developing performers should cater for positive dual effect and negative characteristics so that these may be exploited and moderated appropriately. An integrated and dynamic system, with a holistic integration of clinical and sport psychology, is offered as an essential element of development systems.